Study of voltage sag in power system with six-phase transmission line - Wan Mohd Afiq Nazman, Wan Anuar (2008)
Voltage sags are the short durations in root-mean-square (RMS) rated AC voltage occur during faults may cause miss-operations to the customer’s equipment and loads of power system and recognized as the most important power quality problem. However, this thesis investigate the sag event which is caused by short circuit (three-phase-to-ground fault and six-phase-to-ground fault) on the double three phase transmission line and conversion of phase double circuit to the six phase single circuit transmission line. Six phase were chosen for this project because six phase enhance power transfer capability and becoming the area of growing interest in the power system industry. This thesis also presents the comparisons between voltage reductions at the terminal bus for both three and six phase cases. Simulation at steady state and transient state of the system proposed is simulated using PSCAD/EMTDC. The system that used in this thesis was four buses transmission line. The simulation result shows that converted double three phase to six phase transmission experienced lower voltage sags level at other bus terminal than double three phase system due to three-phase-to-ground fault and six phase-to-ground fault if the fault happen at bus three, but for faulted bus, the it’s experienced the same percentage voltage sag. For fault happen between transformers in six phase operation, 20% to 45% of the voltage was improve at the faulted bus compare to three phase system.